(untitled) - Duigu, Gabi (Oxford, 2001)
Q: Skills for Success, Second Edition is a six-level paired skills series that helps students to think critically and succeed academically. With new note-taking skills, an extended writing syllabus and authentic video in every unit, Q Second Edition equips students for academic success better than ever. Q Second Edition helps students to measure their progress, with clearly stated unit objectives that motivate students to achieve their language learning goals. And the online content, seamlessly integrated into the Student Book, allows teachers to truly implement blended learning into the classroom.
Keywords: Tiếng Anh,English language; Viết,Writing